Frequency and impact of slow flow / no flow in primary percutaneous coronary intervention - Ghazanfer Ali Shah; Tooba malik; Sadaf Farooqi; Salman Ahmed; Khadijah Abid (Journal of the Pakistan Medical Association, 2021)
Objectives: To determine the frequency of slow/no flow in primary percutaneous coronary intervention, to know the clinical and angiographical predictors of the phenomenon, and to investigate the immediate impact of slow/no flow on hemodynamics. Method: The cross-sectional study was conducted at the National Institute of Cardiovascular Diseases, Karachi, from June 2018 to July 2019, and comprised patients presenting with ST elevation myocardial infarction who underwent primary percutaneous coronary intervention. Demographic and clinical details of the patients were recorded. The antegrade flow was assessed and determined using the thrombolysis in myocardial infarction criterion. Patients were assessed for the occurrence, predictors and impact of slow/no flow. Data was analysed using SPSS 21. Results: Of the 559 patients, 441(78.9%) were males. The overall mean age of the sample was 55.86±11.07 years. Angiographical slow/no flow during the procedure occurred in 53 (9.5%) patients, while normal flow was achieved in 506(90.5%). The thrombolysis in myocardial infarction grade in the affected patients was 0 in 10(1.8%), 1 in 15(2.7%), and 2 in 28(5%) patients. Smoking status, Continuous...